Weed Your Budget: Visualizing an Academic Library’s Financial Position - Harlan, Lydia (Information Technology and Libraries, 2025)
This paper presents a case study about opportunities for libraries to elevate reporting on their organization's financial status, transactions, and available funds using data visualization, specifically with Power BI, based on work at University of Oregon Libraries. The Power BI dashboard aggregates data from the university’s financial system and integrated library system to provide a consolidated view, and to tell the library's story in a more engaging way. The author proposes using this type of business intelligence technology to provide a transformative impact on financial operations of libraries.